Influence Of Socioeconomic Deprivation On Short- And Long-Term Outcomes Of Home-Based Pulmonary Rehabilitation In Patients With Chronic Obstructive Pulmonary Disease - Grosbois, Jean-Marie; Robiquet, Justine Heluain; Machuron, François; Terce, Gaelle; Chenivesse, Cécile; Wallaert, Benoit; Le Rouzic, Olivier (International journal of chronic obstructive pulmonary disease, 2019)
Pulmonary rehabilitation (PR) improves exercise tolerance and quality of life in patients with chronic obstructive pulmonary disease (COPD), regardless of disease severity. Socioeconomic deprivation has been linked to the incidence of COPD; however, little is known about its impact on PR outcomes. In this retrospective observational study, 459 COPD patients were enrolled and dichotomized into socially deprived (n=276) and non-socially deprived (n=183) groups based on a cut-off of 30.17 in the EPICES questionnaire (Evaluation of Deprivation and Inequalities in Health Centers), which evaluates socioeconomic disadvantage. The PR program consisted of once-weekly home sessions for 8 weeks, and consisted of an individualized plan of retraining exercises, physical activities, therapeutic education, and psychosocial and motivational support. Exercise tolerance, anxiety and depression, and quality of life were assessed using the 6 min stepper test (6MST), Hospital Anxiety and Depression Scale (HADS), and Visual Simplified Respiratory Questionnaire (VSRQ). Assessments were made before the PR program (baseline) and then at 2 (T2), 8 (T8), and 14 (T14) months after baseline. Compared with the non-socially deprived group, socially deprived patients were younger, more frequently women, active smokers, and living alone, and belonged to lower socioprofessional categories. At baseline, 6MST, VSRQ, and HADS measures were lower for the socially deprived than the non-socially deprived group. At T2, T8, and T14, there were no significant between-group differences in any outcome, and the percentage of patients showing clinically important improvements was the same in both groups. Home-based PR is effective for COPD patients in the short and long term, regardless of socioeconomic status.